Characterization of nanocomposite film based on chitosan intercalated in clay platelets by electron beam irradiation. (10th February 2017) - Shahbazi, Mahdiyar; Rajabzadeh, Ghadir; Ahmadi, Seyed Javad
Graphical abstract: Highlights: At low irradiation doses, crosslinking reaction improved physico-mechanical properties of nanocomposite. Depolymerization of chitosan chains upon high level of irradiation decreased film crystallinity. Irradiated films have a high glass-transition temperature compared with non-irradiated one. Chitosan chains were more intercalated in clay galleries after electron beam irradiation. Abstract: Different electron beam doses (10, 20, 30 and 40 kGy) were tested with the purpose of investigating their influences on chitosan/clay (cloisite 20A) nanocomposite film to improve its functional performance by providing a crosslinked matrix. Water resistance, water contact angle and water barrier property of nanocomposite film were increased up to 30 kGy, and then drastically decreased at the level of 40 kGy. Characteristic diffraction peak of chitosan shifted to low angle with an increase in the interlayer spacing of the nanoclay after 30 kGy irradiation, indicating a superlative intercalation. Crystallinity degree of chitosan/clay nanocomposite was increased in the amorphous region as the irradiation dose increased up to 30 kGy. However, irradiation at level of 40 kGy was converted the crystalline region of nanocomposite film to the amorphous state with losing the chitosan crystallinity. Irradiation increased the film tensile strength due to crosslinking of chitosan chains, with more pronounced effect at 30 kGy and decreased it by chain degradation at 40 kGy. A glass transition temperature was detected in DSC thermogram of chitosan/clay film, and it shifted to higher temperatures as the irradiation dose increased. Moreover, cold-crystallization exothermic peak of the chitosan/clay film moved to the lower temperature after irradiation, suggesting a faster crystallization rate. FE-SEM showed that the chitosan chains were more intercalated between the nanoclay platelets with increasing the irradiation dose. A progressive decrease in the roughness parameters of 20 and 30 kGy irradiated nanocomposite films revealed by atomic force microscopy, whereas irradiation at 40 kGy increased roughness values.